Utilisation of online resources and learning outcomes of undergraduates in Nigerian universities - Fasanmi, Success Ayodeji (Educational Challenges, 2025)
The integration of online learning resources in higher education has profoundly reshaped the educational landscape and the learning outcomes of undergraduates in universities. Purpose. This study examined the utilization of online resources and learning outcomes of undergraduates in Nigerian universities. The study hinges on the connectivism theory. Connectivism theory is considered relevant particularly in the digital age, where technology plays a crucial role in connecting learners to vast amounts of information. Methodology. The study adopted a descriptive survey research design. Obafemi Awolowo University (OAU), which is adjudged to be the leading ICT university in Nigeria, was purposively selected for the study with a sample size of 600 students using a simple random sampling technique. Data was collected using questionnaires, and gathered data were analyzed using descriptive and inferential statistics. Results. The results showed that online resources were seen as valuable tools for improving learning experiences. It further showed that the influence of online resources on academic performance and learning outcomes could vary among individuals, and may depend on factors such as the quality of resources, individual learning styles, and access to technology. The hypothesis tested indicates strong statistical evidence that online resource utilization had a significant influence on the learning outcomes of undergraduates in the study area. Conclusion. The need for educational institutions to improve the accessibility and quality of online resources for their students. The need for policies on the use of online resources to ensure that students use these resources responsibly, and productively was equally recommended.